The Land and Building Tax Information System in Bekasi Municipal - Mita Widyastuti (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2023)
Land and Building Tax is a tax obligation that applies to land and building owners, which also applies in Bekasi City. Land and Building Tax plays an important role in increasing physical and non-physical development. The Regional Revenue Agency increases Regional Original Revenue by implementing the Land and Building Tax Information System (IPBB) to facilitate accurate, fast, responsive and accountable services. This study aims to analyze the effectiveness of the implementation of the Land and Building Tax Information system at the Bekasi City Regional Revenue Agency as well as to describe the obstacles faced and analyze the efforts made in the Land and Building Tax Information system at the Regional Revenue Agency Office. This research paradigm uses constructivism paradigm. The design of this research is a case study. Qualitative research methods with data acquisition techniques using observation, in-depth interviews and literature study with the technique of determining informants. And data analysis techniques using data collection, reduction, data display and drawing conclusions. The results of this study indicate that the system can be said to have been effective. Because it can make it easier for the public to check PBB payments, when taxpayer data is not appropriate, it can be immediately updated. However, there are still obstacles, namely the lack of data collection carried out and socialization that has not been carried out.